TRAINING LOADS OF PLAYERS OF THE NATIONAL JUNIOR NATIONAL TEAM IN SWIMMING - Kreft, P.; Skalski, D. W.; Pęczak-Graczyk, A.; Kowalski, D. (Rehabilitation and Recreation, 2022)
In the above work, an attempt was made to determine the training loads of the players from the national team of juniors in swimming and their impact on the final result in the main competitions. If you want to effectively manage the training process, you should rely on proven ways of influencing the player. Here, the correct selection of training loads is very important, and the search for examples of their effective impact provides valuable training information and application conclusions. The study used research methods in the form of a comparative analysis of training loads in the macrocycle from September to December 2020. Need-data 6 juniors of the Polish national team in swimming were examined, whose influence of training loads on high results in the national rank. 3 girls and 3 boys were examined. All players were 16 years of age. The whole group followed one training program. Checking the data obtained from the analysis made it possible to show information on the amount of training loads in the water of the players in which swimmers were subjected to control starts in September in Wrocław, swimming about 8 km on one training unit, in October 160 km, having a control start in Lublin, swimming about 7 km. In the last 14 days before the main competition, the riders swam about 5.5 km in the first week and 3.6 km in the second. The swimmers followed the same training program. The planned training loads brought the planned results during the Polish Championships, where the players improved their life results so far, winning gold and silver medals. One of the ways to achieve mastery is to find the optimal relationships between the implementation of training loads and changes in the level of the competitor’s training.